Inhibition of macrophage migration inhibitory factor (MIF) suppresses apoptosis signal-regulating kinase 1 to protect against liver ischemia/reperfusion injury - Chen, Sanyang; Yu, Qiwen; Song, Yaodong; Cui, Zongchao; Li, Mengke; Mei, Chaopeng; Cui, Huning; Cao, Shengli; Zhu, Changju (Frontiers in Pharmacology, 2022)
Background: Hepatic ischemia–reperfusion (I/R) injury is a major complication leading to surgical failures in liver resection, transplantation, and hemorrhagic shock. The role of cytokine macrophage migration inhibitory factor (MIF) in hepatic I/R injury is unclear. Methods: We examined changes of MIF expression in mice after hepatic I/R surgery and hepatocytes challenged with hypoxia–reoxygenation (H/R) insult. Subsequently, MIF global knock-out mice and mice with adeno-associated-virus (AAV)-delivered MIF overexpression were subjected to hepatic I/R injury. Hepatic histology, the inflammatory response, apoptosis and oxidative stress were monitored to assess liver damage. The molecular mechanisms of MIF function were explored in vivo and in vitro. Results: MIF was significantly upregulated in the serum whereas decreased in liver tissues of mice after hepatic I/R injury. MIF knock-out effectively attenuated I/R -induced liver inflammation, apoptosis and oxidative stress in vivo and in vitro, whereas MIF overexpression significantly aggravated liver injury. Via RNA-seq analysis, we found a significant decreased trend of MAPK pathway in MIF knock-out mice subjected hepatic I/R surgery. Using the apoptosis signal-regulating kinase 1 (ASK1) inhibitor NQDI-1 we determined that, mechanistically, the protective effect of MIF deficiency on hepatic I/R injury was dependent on the suppressing of the ASK1-JNK/P38 signaling pathway. Moreover, we found MIF inhibitor ISO-1 alleviate hepatic I/R injury in mice. Conclusion: Our results confirm that MIF deficiency suppresses the ASK1-JNK/P38 pathway and protects the liver from I/R -induced injury. Our findings suggest MIF as a novel biomarker and therapeutic target for the diagnosis and treatment of hepatic I/R injury.